Porcine Parvovirus 2 Is Predominantly Associated With Macrophages in Porcine Respiratory Disease Complex - Nelsen, April; Lin, Chun-Ming; Hause, Ben M. (Frontiers in Veterinary Science, 2021)
Porcine respiratory disease complex (PRDC) is a significant source of morbidity and mortality, manifested by pneumonia of multiple etiologies, where a variety of pathogens and environment and management practices play a role in the disease. Porcine reproductive and respiratory syndrome virus (PRRSV), influenza A virus (IAV), and porcine circovirus 2 (PCV2) are well-established pathogens in PRDC. Porcine parvovirus 2 (PPV2) has been identified in both healthy and clinically diseased pigs at a high prevalence worldwide. Despite widespread circulation, the significance of PPV2 infection in PRDC and its association with other co-infections are unclear. Here, PPV2 was detected in the lung tissue in 39 of 100 (39%) PRDC-affected pigs by quantitative polymerase chain reaction (qPCR). Using in situ hybridization (ISH) in conjunction with tissue microarrays (TMA), PPV2 infection was localized in alveolar macrophages and other cells in the lungs with interstitial pneumonia in 28 of 99 (28.2%) samples. Viral load tended to correlate with the number of macrophages in the lungs. Assessment of the frequency, viral titers, and tissue distributions showed no association between infection of PPV2 and other major viral respiratory pathogens. In one-third of the PPV2-positive samples by qPCR, no other known viruses were identified by metagenomic sequencing. The genome sequences of PPV2 were 99.7% identical to the reference genomes. Although intensive intranuclear and intracytoplasmic signals of PPV2 were mainly detected in alveolar macrophages by ISH, no obvious virus replication was noted in in vitro cell culture. Together, these results suggest that PPV2 is associated, but may not be the sole causative agent, with PRDC, warranting the control and prevention of this underdiagnosed virus.